SCIENTIFIC RESEARCH TRENDS OF THE TOURISM SPHERE IN UKRAINE: BIBLIOMETRIC ANALYSIS - Kulyniak, Ihor (Соціальна економіка, 2024)
The study is devoted to the analysis of scientific research trends of the tourism sphere in Ukraine using bibliometric analysis of scientific publications published in the international scientometric database Scopus. The article outlines the current state of the scientific research development in the field of tourism, identifies the most relevant topics and promising directions of research in the tourism sphere of Ukraine. The research methodology includes three main stages: data search and collection, data processing and visualization, as well as analysis of the obtained results. For data collection, the Scopus database was used, with an emphasis on publications containing the keywords “touris*” and “Ukraine” for the period 1977-2024. The author carried out the data processing using the VOSviewer program, which made it possible to build a network map and identify five key clusters that reflect the main directions of research. The identified clusters indicate important aspects such as tourism development and tourism services market, recreation and ecology, economics and management of tourism industry, socio-demographic aspects of tourism, pandemic and technological innovation in tourism. On the basis of the data on the occurrences and the total link strength of the identified keywords, which are used to indicate the types of tourism, the author made conclusions about the specialized tourism development trends in Ukraine. The author found that the scientific attention is focused on the research of tourism types that are related to ecology, sustainable development and agriculture (ecotourism, agritourism, rural tourism), health care (medical tourism) and historical and cultural heritage (heritage tourism, dark tourism, religious tourism). The study analyses the chronological evolution of the publishing activity of researchers. The author revealed a gradual transition from social and environmental issues to the study of economic conditions, technological, innovative development and adaptation to new challenges faced by the tourism sphere in Ukraine in modern conditions. This study is useful for the formation of strategies for the tourism sphere development of Ukraine and the identification of priority topics for further scientific research, taking into account modern trends, challenges and opportunities.